Motivation for weight loss among completers of a free community-based weight loss program in a US-Mexico border region: A self-determination theory perspective - Martinez, Miriam; Salazar-Collier, Cindy L.; Pena, Jessica; Wilkinson, Anna V.; Chavarria, Enmanuel A.; Reininger, Belinda M. (Frontiers in Public Health, 2022)
This study explores the perceptions and motivation for weight loss among participants who completed a free community-based weight loss program in a predominantly Hispanic and low-income region along the US-Mexico border using a Self-Determination Theory (SDT) perspective. This manuscript is timely as qualitative research on the effect of motivation as a factor in behavioral interventions to reduce overweight or obesity is currently lacking. Individual semi-structured interviews were conducted with 20 participants (80%, n=16 female) who completed a community weight-loss intervention to assess motivation for weight loss and participating, and the role of social support and self-efficacy in weight loss. Directed content analysis was used with SDT guiding the questions and subsequent theme analysis. The findings communicate perspectives of participants relevant to 8 prominent themes. The regulation types and constructs related to SDT included: non-regulation, external regulation, introjected regulation, identified regulation, integrated regulation, and intrinsic regulation as well as competence and relatedness. Participants mentioned external sources of motivation, such as wanting to improve their physical appearance, and motivation due to financial incentives. Fewer participants reported intrinsic motivators, which the literature suggests are more likely to create lasting change and improved health behaviors. Understanding the motivation for behavior change and completion of weight loss programs is essential to help participants reach their goals effectively and sustain weight loss. A greater emphasis during weight loss programs on the motives for individuals to lose weight may help improve outcomes in weight-loss interventions. Additionally, increasing strategies targeted at enhancing intrinsic motivation for weight loss may be beneficial.